Factors Influencing the Incident of Underweight Children Under Five Years in Sangihe Regency - Astri Juwita Mahihody; Jelita Siska Herlina Hinonaung (JURNAL INFO KESEHATAN, 2020)
Undernutrition can make children under five years vulnerable to diseases and can even cause death. One indication of children under five years suffering from malnutrition in children under five years is below the red line on the weight chart (underweight). This study aims to identify the factors that most influence the incidence of underweight in Sangihe Regency, North Sulawesi. This research was a quantitative analysis using a research methodology of a cross-sectional sample. For this analysis, the sample was 165 respondents. These variables include education, jobs, income, and infectious diseases. The relationship between education levels, income, experience, and contagious diseases with underweight children was measured less using the chi-square test. In contrast, the determinants of underweight were identified using logistics regression. The results showed that the two most dominant factors that affected the incidence of underweight children under five years were occupational factors (p-value <0.001) and knowledge factor (p-value <0.001). The other factors that might influence the cases of underweight children under five years are knowledge of feeding patterns and the number of children. Conclusion this research is Good knowledge is needed by mothers of children under five years in determining optimal nutrition for children under five years. For this reason, the mother's role is necessary for children under five to help the head of the family in finding additional income so that family nutrition, especially children under five, can be fulfilled.